IMPLEMENTASI PERATURAN BUPATI BOJONEGORO NOMOR 48 TAHUN 2018 TENTANG PROGRAM PETANI MANDIRI - M. Abdim Munib (Universitas Islam Kadiri, 2022)
Regional autonomy is a way for regional governments to accelerate development in order to achieve social welfare. In this context that the policy of the Bojonegoro Regency government presents the independent farmer program which was legalized through Bojonegoro Regent Regulation Number 48 of 2018 concerning the independent farmer program. The research aims to find out and ensure that the policies made by the local government have been effective or there are still obstacles at the implementation level. This research is an empirical legal research aimed at observing the workings of law in society. Based on this research, the results show that the Bojonegoro Regent's Regulations have been implemented properly to provide legal certainty in implementing the program, although there are still obstacles including the short time span for spending capital assistance (production facilities), there are still concerns about conflicts with other regulations, limited number of resources. humans and the need for more massive socialization. Therefore, it can be suggested to improve the Regent's Regulation, optimize human resources and wider socialization so that people can understand the program and access the independent farmer program.